The Technique of Mobilization of the Colon for Pull-Through Procedure in Hirschsprung’s Disease - Bilal, Ruslan; Ospanov, Marat; Dzhenalayev, Damir; Olkhovik, Yuri; Khamitov, Medet; Kozhakhmetov, Arman; Satbekov, Rauan; Abetova, Dina (Frontiers in Surgery, 2022)
In patients with Hirschsprung's disease (HD) persistent obstructive symptoms may develop after surgery. The causes of mechanical obstruction may be retraction of the pulled-through bowel, due to insufficient mobilization of the mesentery, or impaired blood supply in the area of the coloanal anastomosis in the case of excessive ligation of the supplying vessels. Leakage and stenosis are formidable complications and require repeated surgical intervention. The purpose of this study is to describe our experience and short-term results of the developed method: Mobilization of the descending colon for its pull-through during the surgical treatment of the children with Hirschsprung's disease, which allows ensuring good mobility of the descending colon and maintaining blood supply at the same time. Methods reviewed the medical records of 20 patients with recto sigmoid HD, who underwent parietal mobilization of the descending colon with preservation of the marginal artery, sigmoid arteries and ligation of the left colon artery. This method is aimed to increasing the mobility of the brought down bowel and maintaining the blood supply to the distal part of the brought down bowel not only from the superior mesenteric artery, but also from the lower one. The SPSS Statistics 26.0 package was used for statistical analysis. To describe the analyzed data with a normal distribution, the mean values and the error of the mean were used. To determine the differences, the Student's t-test was used, the differences were considered significant at a significance level of p <0.05. Results. In all the patients, the postoperative period was uneventful, without complications. The patients were discharged for outpatient treatment on average on the seventh day after the surgery. In all the cases, there were no signs of anastomotic leakage or stricture on follow-up after 6-12 months. Conclusion. The method of mobilization of the colon in recto sigmoid form of Hirschsprung's disease: parietal mobilization of the descending part of the colon preserving the marginal artery, sigmoid arteries and ligating the left colon artery can reduce the risk of complications by eliminating the tension of the descending colon.